Hubungan Health Locus of Control dengan Kepatuhan Minum Obat pada Penderita Hipertensi yang Masih Aktif Bekerja di Desa Taman Wilayah Kerja Puskesmas IV Abiansemal - Srinadi, Ni Komang; Pramesti, Theresia Anita; Thrisna Dewi, Ni Luh Putu (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Hypertension is a non-communicable disease with an incidence rate that increases annually, while low medication adherence indicates that hypertension management remains suboptimal, particularly among patients who are still actively working. One psychological factor that influences health behavior is health locus of control (HLC), which refers to an individual’s belief regarding control over their health condition. This study aimed to determine the relationship between HLC and medication adherence among hypertensive patients who were still actively working in Taman Village, within the working area of Abiansemal IV Primary Health Center. The study used a descriptive correlational design with a cross-sectional approach and involved 87 respondents selected through purposive sampling. The instruments were the Multidimensional Health Locus of Control (MHLC) questionnaire and the Hill-Bone Compliance to High Blood Pressure Therapy Scale. Data were analyzed using the Spearman Rank correlation test. The results showed that most respondents had a high level of HLC (72.4%) and good medication adherence (74.7%). The Spearman Rank test produced a p-value of 0.000 with a correlation coefficient of 0.410, indicating a statistically significant relationship with moderate strength and a positive direction. These findings indicated that higher HLC was associated with better medication adherence, supported by internal HLC and external factors such as family support and the role of health services, which motivated patients to adhere to treatment consistently